Strategi Guru BK dalam Membangun Kedisiplinan Siswa: Studi Kasus di MAN 2 Mojokerto - Rahmawati, Pudji; Roghibah, Vika Tsalatsun (Institut Agama Islam Negeri Padangsidimpuan, 2025)
This research aims to provide an in-depth description of the strategies employed by Guidance and Counseling (BK) teachers in building student discipline at Madrasah Aliyah Negeri (MAN) 2 Mojokerto. This focus was chosen due to the prevalence of undisciplined behavior among students, such as high rates of tardiness, truancy, leaving class without permission, and various other violations of school rules, which negatively impact the effectiveness of the learning process and character formation. To gain a comprehensive understanding of this phenomenon, this study uses a descriptive qualitative approach, with BK teachers and students as research subjects selected through purposive sampling techniques. Research data was obtained through in-depth interviews, direct observation of student behavior, and documentation in the form of violation records and school reports. The research findings indicate that guidance and counseling teachers employ various strategies in fostering student discipline, including individual counseling, group counseling, information services, classical guidance, educational sanctions, and ongoing coordination with homeroom teachers and subject teachers. The approach used does not solely focus on rule enforcement but emphasizes preventive and educational aspects aimed at cultivating self-awareness, a sense of responsibility, and students' intrinsic motivation to comply with school rules. These findings confirm that the role of guidance and counseling teachers is highly significant in shaping a sustainable culture of discipline and supporting the creation of a conducive learning environment oriented toward student character development